Imposing zakāt on legal entities and its applications in Islamic financial institutions - Mohd Noor, Azman; Haron, Muhamad Nasir (Brill Academic Publisher, 2013)
Zakāt (obligation to donate a certain proportion of wealth each year to charitable causes) is imposed on particular assets owned by Muslims. However, as there has been a tremendous development in trade locally and globally, and with the growth of Islamic banking and finance and the increased demand for Sharīʿah-compliant services and supplies, a number of contemporary Muslim scholars have suggested that zakāt be imposed on legal entities. This implies that the calculation is based on the company’s net asset value. Based on this proposition, one need not know the identities of the shareholders: i.e., whether they are government-linked companies, foreign parent companies, individual proprietors, Muslims or non-Muslims. This article aims to examine the validity of imposing zakāt on legal entities from the Sharīʿah’s perspective.